How being female impacts learning and career growth in advertising creative departments. Issue 1 (5th January 2015) - Windels, Kasey; Mallia, Karen L.
Abstract : Purpose: – In the male-dominant creative industries, do men and women have access to the same resources for career learning and development? The purpose of this paper is to examine women's perspectives of their career trajectories in advertising creative departments. Design/methodology/approach: – Situated learning theory views learning as produced through interaction with and increasing participation in a community of practice. Interviews were conducted with 19 female creatives to examine two research questions: first, how do women develop identities as creative practitioners within the male dominated advertising creative department? and second, how are women's learning trajectories influenced by their gender? Findings: – Gendered expectations affected the type of work women were supposed to produce, their ability to sell work, and the types of assignments they received. Women lacked legitimacy and experienced difficulties developing an identity as a master practitioner. They instead emphasized parts of their identity unrelated to the profession. Research limitations/implications: – Women were unable to develop identities as full members of the community of practice. The identity formed in conjunction with work was that of a person with lesser talents, fewer opportunities, and less valued contributions, causing them to exit the field or seek positive identity from places other than work. Originality/value: – This study was the first study that the authors are aware of to examine empirically the relationship between situated learning theory and gender. It provided evidence from women's perspectives that gender restricted access to material for forming a positive work-identity, which impeded learning as women realized and accepted they were on a different trajectory than similarly-situated males.